2022
DOI: 10.3390/met12071232
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study and Investigations of Bead Geometries of GMAW-Based Wire–Arc Additive Manufacturing of 316L Stainless Steels

Abstract: Appropriate selection of wire–arc additive manufacturing (WAAM) variables imparts bead geometries with characteristics of multi-layer structures. Thus, the present study aimed to optimize the gas metal arc welding (GMAW)-based WAAM variables of travel speed (TS), wire feed speed (WFS), and voltage (V) for the bead geometries of bead width (BW) and bead height (BH) on an SS 316L substrate. Single-layer depositions were made through a metallic wire of SS 316L by following an experimental matrix of the Box–Behnke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The TS trend shows that the BW decreased with an increase in TS. This happened because, with higher TS, less metal could be dropped on the same position, leading to less deposition and, thus, smaller BW [ 25 ]. Finally, with higher values of GMR, the BW caused an insignificant change as, at first, it decreased and then increased, negating the changes or uncertainties caused.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TS trend shows that the BW decreased with an increase in TS. This happened because, with higher TS, less metal could be dropped on the same position, leading to less deposition and, thus, smaller BW [ 25 ]. Finally, with higher values of GMR, the BW caused an insignificant change as, at first, it decreased and then increased, negating the changes or uncertainties caused.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the mechanical properties of the part made from the optimized process parameters were excellent, showing the importance of optimization. Chaudhari et al [ 25 ] studied the effect of WAAM process parameters on a bead’s geometry for single-layer deposition, such as BW or BH, with the variance of parameters such as TS, WFS, and V. They used a Box–Behnken design for singe-layer deposits and found that WFS was the most significant factor for both BW and BH, followed by V and TS. Their study revealed that a multi-layered structure was successfully fabricated at optimized parametric settings at a TS at 141 mm/min, a WFS at 5.50 m/min, and a voltage of 19 V. Natryan et al [ 26 ] used the Taguchi technique to study the effects of TS, welding current, and filler diameter on the quality of welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of variance (ANOVA) was employed to determine the suitability and importance of the parameters. For ANOVA, 95% of CI was considered, which means p value lowers than 0.05 depict the impact of selected variables to affect the selected response [60,61]. The influence of the machining variables on responses was then investigated, using main effect graphs for individual regression models.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been a growing trend towards the application of Hastelloy C-22 weld overlay on SA 240 Type 316L in various industries, including petrochemicals. Due to the greater heat resistance properties of stainless steels, they are largely preferred in chemical, oil, gas, and petrochemical sectors [39,40]. This trend is driven by the need for materials that can withstand highly corrosive environments, maintain structural integrity, and reduce maintenance costs [41].…”
Section: Introductionmentioning
confidence: 99%